(untitled) (Research, Society and Development, 2022)
Objective: To discuss the factors related to stress in nurses who worked during the pandemic of COVID-19, describing the relationship between both and identifying the main coping strategies that were used to mitigate these factors. Methodology: This is a descriptive, qualitative, exploratory literature review, which was conducted within the BVS, LILACS, LIVINO and Scielo databases using the following descriptors: "COVID-19", "stressors" and "nursing", selecting articles on the subject between 2017 and 2022 and excluding those with incomplete texts. Results: We identified some types of psychological illness in nurses and that the most recurrent stressors during the COVID-19 pandemic were stress, depression, anxiety, and Burnout Syndrome. It was also found that the strategies used to face these stressors were: the creation of a space for psychosocial care where these professionals could expose themselves, create a support group and watch educational videos about quality of life and mental health at work. Final Considerations: The emergence of COVID-19, a highly transmissible disease, forced health services to adapt to the reality of the situation in order to face it. The nursing professionals had their daily life changed and the excessive workload generated psychological stress, social, behavioral, family and values challenges that impact their lives in this period of pandemic and it was observed the minimum of strategies that could avoid the stressors.